KEBIJAKAN SMART CITY DALAM PENERAPAN SISTEM PEMERINTAHAN DI KOTA SEMARANG - Elfrida T. F. Aindita; Irfan Setiawan (Institut Pemerintahan Dalam Negeri (IPDN), 2022)
The application of technology in government has gone global in various countries. The use of communication and information is no longer limited by space and time. One world feels in our hands through electronic devices and internet access. There are so many of them who take advantage of this opportunity to take advantageous opportunities to improve their standard of living. This study aims to analyze the application of a smart city in the city of Semarang, and the things that hinder the application of the smart city concept. This study uses a qualitative descriptive analysis method. This study observes the government's actions in taking a smart city implementation policy. The city of Semarang has a personal branding as one of the big cities in Indonesia which incidentally has many advantages in terms of infrastructure. Semarang in realizing its consistency in building a website that can be accessed by everyone related to smart cities as a form of implementing these policies where on the website there are facilities for smart governance, smart branding, smart economy, smart living, smart society, and smart environment. The implementation of smart city in Semarang City is still undergoing gradual changes and there are still many shortcomings that need to be overcome. The slow implementation process is certainly affected by the existing obstacles both from within and from outside the Semarang City Government.